The Role of Bugis Tabe’ Culture in Enhancing Politeness Strategies in English Classrooms AT SD IT Al-Iman Uluale, Sidrap - Putri, Selviana; Hermansyah, Sam; Aisa, Sitti (Universitas Muhammadiyah Enrekang, 2026)
This study aimed to explore the role of Bugis tabe’ culture in enhancing students’ politeness strategies in English classroom interaction at SDIT Al-Iman Uluale, Sidenreng Rappang Regency. The study also examined how the cultural values embedded in tabe’ influenced students’ verbal and non-verbal communication during English learning activities. This research employed a descriptive qualitative approach. The data were collected through classroom observations, semi-structured interviews, and documentation. The participants of this research consisted of one English teacher and sixth-grade students at SDIT Al-Iman Uluale. The data were analyzed using an interactive qualitative analysis model, including data reduction, data display, and conclusion drawing to identify patterns of politeness strategies used by students during classroom interaction. The findings revealed that Bugis tabe’ culture plays an important role in shaping students’ politeness strategies in English classroom interaction. Politeness was reflected through verbal expressions such as polite words, indirect utterances, and respectful language forms. In addition, non-verbal behaviors such as respectful posture, soft tone of voice, and appropriate turn-taking were also observed during classroom communication. The students also practiced multilingual politeness strategies by combining Bugis, Indonesian, and English expressions to maintain respect and clarity when interacting with the teacher. In conclusion, the integration of Bugis tabe’ cultural values in English learning supports the development of polite and respectful communication among students. It also contributes to creating a positive and conducive classroom environment while strengthening students’ character and cultural awareness in the learning process.